Anti-hypertensive Effect of Cereal Antioxidant Ferulic Acid and Its Mechanism of Action - Alam, Md. Ashraful (Front Nutr, 2019)
Ferulic acid is a simple phenolic acid found mainly in cereals and grains, used as an antioxidant and food preservative. Recent evidence suggests that ferulic acid possess anti-inflammatory, anti-diabetic, anticancer, and cardioprotective properties. Several investigations also have shown that ferulic acid rich food might prevent hypertension. As a potent scavenger of free radicals (ROS, reactive oxygen species), ferulic acid attenuates oxidative stress, which is responsible for lowering elevated blood-pressure through improved endothelial function and increased bioavailability of the nitric oxide in the arterial vasculature. This review article describes the role of ferulic acid in the pathophysiology of vascular dysfunction and hypertension along with highlighted the merit of further scientific and clinical exploration.